Women in Ministry: Re-Reading 1 Corinthians 14:33-35 in the 21st Century Context - Adetunji, Emmanuel Olujide; Afolaranmi, Adebayo Ola (Universitas Pelita Harapan, 2024)
First Corinthians 14:33-35 reveals one of the many controversies about the roles of women in ministry in the church today. Many scholars have given diverse interpretations of the verses. The verses have led many people, including many Christian denominations, to have some positions on women in ministry. The thrust of this article is to explore the correct interpretation of the verses based on some historical and biblical perspectives. The work adopted the historical and biblical exegesis method. Feminism theory was also considered in the work. The work concluded that 1 Corinthians 14:33-35 should not be interpreted literally. It must be interpreted within its context. It also concluded that women have their roles to play in the world and in the propagation of the gospel of Christ, regardless of attempts by men to relegate them to the background.